AEROMAGNETIC INVESTIGATION OF GEOLOGIC STRUCTURES ASSOCIATED WITH GOLD MINERALIZATION ALONG DANJA, NORTHWESTERN NIGERIA - USMAN, A.; SANI, M.A.; LAWAL, K.M.; MAGAJI, S.S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
The discovery of petroleum led to a subsequent shift of the Nigerian economy, leading to a lack of attention to gold exploration, despite the widespread potentials. Gold production declined during the Second World War period and never recovered as mines were abandoned by mostly colonial companies, hence the need to study the aeromagnetic field over the study area. the interpreted aeromagnetic data delineate structures associated with mineralization of gold along Danja, North Western Nigeria. This was achieved by first determining depth to basement and then producing a magnetization map showing susceptibility range across the entire area of study, and to model the shape, location and depth of structures in the study area. The anomalies on the aeromagnetic map were defined by fitting a first order polynomial to the total fields, by the method of least squares to obtain the residual field data. First vertical derivative and analytic signal anomalies computed, defined distinct pattern of the magnetic signatures. Euler deconvolution applied produced solutions at different location of the area of study, this shows that the solution plotted clustered around the region where the geological structures are located with average depths range of 200.2 m to 2229.1 m, with very few solutions having depths less than 300 m, the most prominent lineament and all major subtle lineament have a depth range of 200 m to 600 m. Most of the solutions within the mining site are between 200.2 m to 618.4 m which shows that the structure is deep seated. The possible flow of fluid that produced the emplacement of Gold mineralization in the area is believed to be related to the Kalangai fault which trends NE-SW along Malumfashi in the study area. The susceptibility values obtained from the magnetization map ranges from -0.000666 to 0.000996SI.